Experiências e sabres de vida em narrativas de mulheres negras - Cavalcante, Simone Joaquim (2019)
The review of academic production regarding the knowledge and non-school educational processes of older black women is a topic still little explored in education researches and a challenge for academic researches. Looking at social reality, it can see that this is also a group of poor or no visibility. Given this scenario, the study started from the following question: how were the non-school knowledge of Luiza Lopes da Silva (Lalu) and Maria de Lourdes Ferreira Gomes constituted over eight decades of existence? The objective of this research was to understand their non-school educational processes, from the core of senses: ways of being women, interdicted dreams, knowledge about plants, taste for letters and community work. Lalu Lopes and Lourdes Ferreira (they have been chosen as participants and collaborators of the study) present common points in their non-school knowledge. Both of them were born in the 1930s, they know the uses of medicinal plants/herbs from rural areas, they are daughters of farmers, they studied the early years of basic education and selfdescribed black. They also differ, being a poet and the other popular educator, positioning themselves as a female subject in the world, in their ways of being, acting, existing and resisting. This thesis, conducted between 2015 and 2019, is based on the theoreticalmethodological approaches of narrative research articulated with feminist studies, based on Feminist Epistemology, and brings the narratives and appreciation of women's experience. It also implies the recognition and importance of non-school knowledge carried out by women research subjects, evoked by experience and transmuted in the narrative. The thesis indicates that investigating and understanding non-school educational processes, through the experiences and life history of these elderly (octogenarian) black women, allows us to think about other ways of producing and acquiring knowledge, in which the learn-teach relationship is not limited to, formal institutional structures in schools and academic centers. In the stories of Lalu Lopes and Lourdes Ferreira and their knowledge, their experiences brought in their narratives break down the barriers of social and academic silence and cross the boundaries of invisibility in educational research.